Kreativitas Mengajar Guru Berdasarkan Kajian Filosofi Pendidikan Kristen - Dianty Greas Athalya Hutagalung; Wiyun Philipus Tangkin (Jurnal Shanan, 2023)
Teaching creativity needs to be owned by the teacher in creating an interesting and fun learning process for students. This is important for the world of education because education is an activity in the learning process to develop all aspects of students. Teaching creativity refers to the important role of the teacher in the classroom so that the teacher should be able to carry out his role properly in the learning process, namely by designing a creative and innovative learning process. Creative teachers are teachers who have new ideas for teaching. This aims to create an effective learning process and can attract students' learning interests. If studied based on the philosophy of Christian education, teachers need to maximize their roles and responsibilities in accordance with the truth of God's Word. Writing scientific papers aims to describe the creativity of teaching teachers. This research was written using the literature review method. The conclusion of this study is that Christian teachers also need to have creative teaching on the right basis according to the philosophy of Christian education. As a suggestion, in the future, the teacher needs to create a learning process that is monotonous and seems boring, but learning is interesting and fun but still pays attention to the learning needs of students in the classroom through fulfilling educational components such as learning methods, learning strategies, techniques, and so on creatively to achieve the learning objectives to be achieved.